(untitled) - Goodrick, Edward W.; (1913-1992) (Great Britain, 1990)
This concordance, a word index arranged alphabetically with more than 35,000 Scripture reference entries, contains contexts for every occurrence of 1,239 key words in the New International Version of the Bible. Special entries for 260 Bible characters are also included.
Keywords: Bible -- Concordances, English -- New International